2020
DOI: 10.3390/foods9060840
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Analysis of the Nutritional Components and Antioxidant Activities of Different Brassica juncea Cultivars

Abstract: The purpose of this study was to compare the nutritional components and antioxidant activities of two different cultivars of Brassica juncea (Dolsan, Yeosu, Korea (BJD) and (Jeongseon, Gangwon, Korea (BJJ)). We investigated the proximate composition (moisture, crude ash, crude protein and crude lipid), antioxidant activities (2,2-Diphenyl-2-picrylhydrazil (DPPH) scavenging activity and ferric reducing antioxidant power (FRAP)), total phenol content, total flavonoid content and sinigrin content by high-performa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
1
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 20 publications
0
11
1
1
Order By: Relevance
“…However, studies have only been conducted on B. juncea cultivated in Dolsan, Yeosu, Korea, and not on B. juncea cultivated in Jeongseon (BJJ). In previous studies, we confirmed that the phenol and flavonoid content of BJJ is higher than that of BJD, and accordingly, the possibility of using BJJ as a health functional food material has been evaluated (Kwon et al, 2020). Therefore, we established an extraction method that can optimize the content of sinigrin in the BJJ extract, and investigated the antioxidant and antiobesity effects of the extract.…”
Section: Introductionmentioning
confidence: 55%
See 2 more Smart Citations
“…However, studies have only been conducted on B. juncea cultivated in Dolsan, Yeosu, Korea, and not on B. juncea cultivated in Jeongseon (BJJ). In previous studies, we confirmed that the phenol and flavonoid content of BJJ is higher than that of BJD, and accordingly, the possibility of using BJJ as a health functional food material has been evaluated (Kwon et al, 2020). Therefore, we established an extraction method that can optimize the content of sinigrin in the BJJ extract, and investigated the antioxidant and antiobesity effects of the extract.…”
Section: Introductionmentioning
confidence: 55%
“…These results were similar to the reduction of lipid accumulation in the present study, indicating that BJJ extract and sinigrin effectively inhibited ROS production, resulting in an antiobesity effect. In a previous study, we reported that about 34.81 mg rutin equivalent/g of flavonoid compounds are present in BJJ extract, which has excellent antioxidant efficacy (Kwon et al, 2020). In this study, the ROS reduction efficacy in adipocytes is thought to have a major effect on antioxidant activity due to the complex action of flavonoid components in BJJ extract.…”
Section: Discussionmentioning
confidence: 75%
See 1 more Smart Citation
“…Rios et al, (2014) addressed the importance of raw fats and oils for modified-food products, such as bakery, sauces, margarine and confectionery. As compared with the study Brassica species, Kwon et al, (2020) reported a low value of crude protein (1.5%) in Brassica juncea cultivars in Korea. The percent of carbohydrates was significantly different between shoots and roots of the two Brassica species.…”
Section: Proximate Composition Minerals and Bioactive Secondary Metamentioning
confidence: 52%
“…Senyawa fenolik yang terdapat pada tanaman dilaporkan memiliki fungsi antioksidan yang tinggi. Ketika kandungan polifenol total meningkat, aktivitas fisiologis, seperti antioksidan akan meningkat (Kwon et al, 2020). Fenolik tersebar luas…”
Section: Pembahasanunclassified